Three-Dimensional Finite Element Modeling of Soft Rock Tunnel With Large Section: A Case Study - Zhang, Junyun; He, Zhuoling; Yu, Xu (Frontiers in Physics, 2020)
With deep-buried depth, large span, high geo-stress, complex geological conditions, and its large sections, the deformation behavior of the Gaopo Tunnel is a complex three-dimensional problem. To reveal the deformation behavior of the tunnel, this paper establishes a three-dimensional model by benching tunnelling method, and compares the monitoring data to analyze the deformation behavior of the surrounding rock and the variation of the stress field in the support structure. The results demonstrate that the rock layer inclination angle is 4° to 10°, the gently inclined layered structure, with the maximum horizontal principal stress direction close to the tunnel trend, which is the main factor for the asymmetric deformation behavior of soft rock tunnel with large section passing through coal seams. This deformation of surrounding rock and the stress of support are obviously restricted by its gently inclined layered structure.